Replisome Assembly at Bacterial Chromosomes and Iteron Plasmids - Wegrzyn, Katarzyna E.; Gross, Marta; Uciechowska, Urszula; Konieczny, Igor (Frontiers in Molecular Biosciences, 2016)
The proper initiation and occurrence of DNA synthesis depends on the formation and rearrangements of nucleoprotein complexes within the origin of DNA replication. In this review article, we present the current knowledge on the molecular mechanism of replication complex assembly at the origin of bacterial chromosome and plasmid replicon containing direct repeats (iterons) within the origin sequence. We describe recent findings on chromosomal and plasmid replication initiators, DnaA and Rep proteins, respectively, and their sequence-specific interactions with double and single stranded DNA. Also, we discuss the current understanding of the activities of DnaA and Rep proteins required for replisome assembly that is fundamental to the duplication and stability of genetic information in bacterial cells.